2019
DOI: 10.14740/gr1185
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Reliability of the Endoscopy and Sedation-Assisted High-Resolution Esophageal Motility Assessment

Abstract: Background Esophageal high-resolution manometry (HRM) is performed for evaluation of dysphagia or the pre-operative evaluation before esophageal surgery. The esophageal manometry parameters, interpreted as per the Chicago classification (CC), are meant to be acquired in an awake state. At times, the patient intolerance or inability to traverse the manometry catheter across the esophagogastric junction (EGJ) renders incomplete esophageal motility evaluation; hence, sedation or endoscopy assistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Studies support that trans-nasal catheter placement fails in 6% to 19% of patients and this is primarily related to discomfort and abnormal anatomy. 3,4,16 Thus, endoscopic placement under conscious sedation has been used to improve comfort of placement and help place the catheter through the EGJ in patients with achalasia and large hernias. However, 2 factors related to this practice could potentially result in differences in manometry metrics and diagnosis: the impact of sedation and the impact of thermal pressure drift.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies support that trans-nasal catheter placement fails in 6% to 19% of patients and this is primarily related to discomfort and abnormal anatomy. 3,4,16 Thus, endoscopic placement under conscious sedation has been used to improve comfort of placement and help place the catheter through the EGJ in patients with achalasia and large hernias. However, 2 factors related to this practice could potentially result in differences in manometry metrics and diagnosis: the impact of sedation and the impact of thermal pressure drift.…”
Section: Discussionmentioning
confidence: 99%
“…1 Additionally, previous studies have reported sedationassisted esophageal manometry, which may aid completion of manometry for patients who could not tolerate the test during awake placement of the manometry catheter. [2][3][4] Placing the catheter while the patient is under sedation can help mitigate some of the discomfort and help complete the exam. Additionally, some situations require endoscopic-guidance of the manometric catheter to achieve the necessary positioning across the esophagogastric junction, eg, esophageal tortuosity with large hiatal hernia or achalasia.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this would suggest that scheduling times between EGD and HRM do not need to be delayed. Further, approximately 7% of patients undergoing HRM may require sedation for accurate placement of the HRM catheter due to intolerance or anatomic considerations, including endoscopic assistance 34,35. Our findings suggest that administration of midazolam and opiates for a same-day endoscopy in such cases likely does not undermine the validity of the HRM findings.Our study has several key limitations.…”
mentioning
confidence: 82%
“…These restraint devices can also facilitate free-feeding protocols during which the dog voluntarily consumes liquid and solid boluses (41,166,198). However, sedation could still be required to calm anxious dogs to facilitate the study, which can potentially alter esophageal motility (201) and sphincter tone (199). Furthermore, stressed, anorexic, or severely ill dogs may refuse to voluntarily prehend the bolus, requiring force-feeding practices that increase the risk of aspiration pneumonia or pre-empt a complete evaluation.…”
Section: Challenges and Limitationsmentioning
confidence: 99%